Autoantibody Repertoire in APECED Patients Targets Two Distinct Subgroups of Proteins - Fishman, Dmytro; Kisand, Kai; Hertel, Christina; Rothe, Mike; Remm, Anu; Pihlap, Maire; Adler, Priit; Vilo, Jaak; Peet, Aleksandr; Meloni, Antonella; Podkrajsek, Katarina Trebusak; Battelino, Tadej; et al. (Frontiers in Immunology, 2017)
High titer autoantibodies produced by B lymphocytes are clinically important features of many common autoimmune diseases. APECED patients with deficient autoimmune regulator (AIRE) gene display a broad repertoire of high titer autoantibodies, including some which are pathognomonic for major autoimmune diseases. AIRE deficiency severely reduces thymic expression of gene-products ordinarily restricted to discrete peripheral tissues, and developing T cells reactive to those gene-products are not inactivated during their development. However, the extent of autoantibody repertoire in APECED and its relation to thymic expression of self-antigens are unclear. We here undertook a broad protein array approach to assess autoantibody repertoire in APECED patients. Our results show that APECED patients display high inter-individual variation in their autoantigen profiles, which collectively are enriched in evolutionarily conserved, cytosolic and nuclear phosphoproteins. The APECED autoantigens have two major origins; proteins expressed in thymic medullary epithelial cells and proteins expressed in lymphoid cells. These findings support the hypothesis that specific protein properties strongly contribute to the etiology of B cell autoimmunity.